PENERAPAN DAM LP (Lepas Pantai) MENUJU INDONESIA BEBAS BANJIR ROB, PEMBANGKIT ENERGI ALTERNATIF DAN PENYEDIA AIR TAWAR BAGI KAWASAN DAERAH PESISIR INDONESIA - Annisa, Mutiara; Chamdalah, Siti; Juniati, Eva; Hutama, Isha Frandika; Irsyad, Ilham Khoirul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
With the increasing volume of sea water due to global climate change in the coastal area is very prone to rob (flood). Indonesian mainland will automatically narrowed since eroded by sea water which swept the coast. Construction of a structure to prevent it are necessary. So dam offshore is the right solution to reduce the problem of marine activities which lead to the reduction of the Indonesian mainland. In addition this structure also has a variety of functions, among others, is a provider of fresh water and alternative energy generation for coastal communities. Application of offshore dam would improve the welfare of people, especially in the coastal areas of Indonesia.